Global Phylogeny and Taxonomy of the Wood-Decaying Fungal Genus Phlebiopsis (Polyporales, Basidiomycota) - Zhao, Ya-Nan; He, Shuang-Hui; Nakasone, Karen K.; Wasantha Kumara, K. L.; Chen, Che-Chih; Liu, Shi-Liang; Ma, Hai-Xia; Huang, Man-Rong (Frontiers in Microbiology, 2021)
An in-depth study of the phylogeny and taxonomy of the corticioid genus Phlebiopsis (Phanerochaetaceae) was conducted. Phylogenetic analyses of the ITS1-5.8S-ITS2 and nrLSU sequences demonstrated that Phlebiopsis is a strongly supported clade that is distinct from its sister clade that includes Phaeophlebiopsis, Hapalopilus and Rhizochaete. Two genera, Australohydnum and Hjortstamia, are reduced to synonyms under Phlebiopsis because generic type species A. griseofuscescens and H. friesii, respectively, are embedded in the Phlebiopsis clade. Twenty-four lineages are resolved in the ITS phylogenetic tree of Phlebiopsis, including six new taxa from Sri Lanka and China — P. albescens, P. brunnea, P. cylindrospora, P. magnicystidiata, P. membranacea and P. sinensis. Five new combinations are proposed — Phaeophlebiopsis mussooriensis, Phlebiopsis bambusicola, P. dregeana, P. griseofuscescens and P. novae-granatae. Phlebiopsis crassa is a morphological species complex with three distinct lineages. Phlebiopsis lamprocystidiata is determined to be a later synonym of P. darjeelingensis. The new taxa are described, illustrated, and compared and contrasted to morphologically similar species. An emended description of Phlebiopsis is provided along with an identification key to 27 accepted species.